Precocious detection of breast cancer in Crato-CE - Fátima Antero Sousa Machado; Francisco Cleudy Amorim; Andrea Gomes Linard (Universidade de Fortaleza, 2003)
This study aims to describe and assess early diagnosis of breast cancer in women in the city of Crato, CE - Brazil. Two semi-structured interviews were applied to patients and nurses of Family Health Centers. Results show that a few professional nurses in ill equippedfacilities make effective use of breast examination techniques. However, patientsknow little about breast self-examination (BSE) and its importance, rarely performing it. The authors believe the necessary quality improvement involve professional and managerial staff in order to reach all patients.